THU0430 Description and prognosis factors of systemic sclerosis-associated interstitial lung disease outcome on serial hrct. (12th June 2018) - Forestier, A.; le gouellec, N.; duhamel, A.; kramer, G.; perez, T.; sobanski, V.; morell dubois, S.; lambert, M.; hatron, P.-Y.; hachulla, E.; behal, H.; matran, R.; et al.
Abstract : Background: Interstitial lung disease (ILD) is a leading cause of morbidity and mortality in systemic sclerosis (SSc). While factors associated with the presence of ILD in SSc (SSc-ILD) are identified, those associated with ILD outcome are still debated and studies assessing the evolution of SSc-ILD on HRCT are scarce. Yet, it is important to identify patients at risk of SSc-ILD worsening because those patients are thought to benefit the most from immunosuppressants. Objectives: Thus, the aims of our study were: to describe the evolution of HRCT extension and patterns of SSc-ILD, to identify baseline prognosis factors of ILD outcome on serial HRCT and to investigate whether the evolution of pulmonary function tests (PFTs) parameters correlated with the evolution on HRCT. Methods: We included 58 SSc patients with HRCT proven ILD, with at least two available HRCT, and collected clinical, biological data and PFT at baseline. We collected all HRCT and PFTs available during follow-up. We modelized PFTs and HRCT evolution using linear mixed model with random coefficients. Results: Mean ILD extension at baseline was 32.3%±28.7%. During a mean follow-up of 5.3±4.9 years, we found a significant mean progression of ILD extension of 0.92%±0.36% per year (p=0.018). Male sex, anti-topoisomerase 1 antibodies, diffuse cutaneous SSc were associated with faster progression of ILD extension. Limited ILD according to Goh et al. staging system, and a coarseness score at zero (meaning 100% of ground glass opacification) were associated with a faster progression of ILD extension. We also found a significant decline of DLCO, FVC and TLC during follow-up. There was a significant correlation between the progression of ILD extension on HRCT and the decline of DLCO, but not with the evolution of FVC. Conclusions: Male patients, patients with diffuse SSc/antitopoisomerase 1, patients with less severe and less extensive ILD at baseline were more likely to experiment a faster progression of ILD extension on serial HRCT. To our knowledge, this is the first study that clearly highlighted the diffuse form of SSc/presence of antitopoisomerase 1 as a worsening factor of SSc-ILD on HRCT. FVC might not be the best mirror of ILD progression while DLCO significantly correlated with change in ILD extension. Our study helps to define the profile of patients who are going to experience a progression of ILD on HRCT during follow up. Disclosure of Interest: None declared